Fertility-sparing treatment for a giant borderline ovarian tumor in an adolescent: a case report - Keying Wang; Tong Wei; Mubiao Liu (Journal of Clinical Technology and Theory, 2026)
Borderline Ovarian Tumors (BOTs) are common ovarian epithelial tumors with biological behavior between benign and malignant lesions. The annual incidence of BOTs is approximately 4.5 per 100,000 population, which increases with age, starting from the 15–19 age group and peaking at 55–59 years. However, BOTs occurring in adolescents accompanied by giant tumors have a relatively low incidence and are rarely reported in the literature. This article reports the clinical diagnosis and treatment process of a 14-year-old adolescent with a giant borderline ovarian tumor complicated by ovarian pedicle torsion. The clinical features, intraoperative management and postoperative outcomes were reviewed, and the key points of diagnosis and treatment of this disease were analyzed in combination with relevant literature, so as to improve clinicians' understanding of this disease. At present, fertility-sparing surgery is the main treatment modality for BOTs patients with fertility needs. Postoperative chemotherapy and other supplementary treatments are not routinely recommended, and long-term follow-up is required after surgery.